Pulmonary Cryptococcosis - Chang, C. C.; Sorrell, T. C.; Chen, S. C.-A. (Seminars in Respiratory and Critical Care Medicine, 2015)
Inhalation of Cryptococcus into the respiratory system is the main route of acquisition of human infection, yet pulmonary cryptococcosis goes mostly unrecognized by many clinicians. This delay in diagnosis, or misdiagnosis, of lung infections is due in part to frequently subtle clinical manifestations such as a subacute or chronic cough, a broad differential of diagnostic possibilities for associated pulmonary masses (cryptococcomas) and, on occasion, negative respiratory tract cultures. Hematogenous dissemination from the lung can result in protean manifestations, the most severe of which is meningoencephalitis. There are few clinical studies of pulmonary cryptococcosis and its pathogenesis is poorly understood. The main purpose of this review is to describe the epidemiology, clinical presentation, diagnosis, and treatment of pulmonary cryptococcosis to increase clinician's awareness of this diagnostic possibility and to enhance clinical management. Useful pointers to the approach and management of pulmonary cryptococcosis and the implications of disseminated disease are included, together with recommendations for future research.
Keywords: pulmonary cryptococcosis; C. neoformans; C. gattii; cryptococcomas; invasive fungal disease